Analysis of the accumulated energy by thermal stratification of liquid inside storage tanks with porous layers - del Rio Oliveira, Santiago; Padilha, Alcides [UNESP]; Scalon, Vicente Luiz (Taylor & Francis Inc, 2008)
A mathematical model was developed in order to study the behavior of thermal stratification of liquid in a typical storage tank with porous medium. The model employs a transient stream function-vorticity formulation to predict the development of stream function and temperature fields in a charging process. Parameters analyzed include Biot, Darcy, Reynolds and Richardson numbers, position, and the thickness of the porous medium. The results show the influence of these physical parameters that should be considered for a good design of storage tanks with thermal stratification.